2018
DOI: 10.1016/j.edurev.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Effective differentiation Practices:A systematic review and meta-analysis of studies on the cognitive effects of differentiation practices in primary education

Abstract: Effective differentiation Practices: A systematic review and meta-analysis of studies on the cognitive effects of differentiation practices in primary education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
197
2
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(226 citation statements)
references
References 61 publications
10
197
2
17
Order By: Relevance
“…Parsons et al (2018) even stated that adapting instruction is "a cornerstone of effective instruction" (p. 206) and "considered the gold standard teachers should strive for" (p. 206). This is not an easy task; differentiated instruction (DI) is regarded as a complex teaching skill (Deunk, Doolaard, Smale-Jacobse, & Bosker, 2015; Van de Grift, Van der Wal, & Torenbeek, 2011). Research by the Dutch Inspectorate of Education (Inspectie van het Onderwijs, , 2015aOnderwijs, , 2015b showed that teachers insufficiently adapt their instruction to student differences.…”
Section: Differentiation As Part Of Teaching Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Parsons et al (2018) even stated that adapting instruction is "a cornerstone of effective instruction" (p. 206) and "considered the gold standard teachers should strive for" (p. 206). This is not an easy task; differentiated instruction (DI) is regarded as a complex teaching skill (Deunk, Doolaard, Smale-Jacobse, & Bosker, 2015; Van de Grift, Van der Wal, & Torenbeek, 2011). Research by the Dutch Inspectorate of Education (Inspectie van het Onderwijs, , 2015aOnderwijs, , 2015b showed that teachers insufficiently adapt their instruction to student differences.…”
Section: Differentiation As Part Of Teaching Qualitymentioning
confidence: 99%
“…Each of these definitions stresses the adaptation of aspects of instruction to differences between students. However, it remains uncertain what "high-quality" adaptations are, how this is enacted in classrooms, and what is required from teachers (Deunk et al, 2015;Park & Datnow, 2017). To obtain insights into the practice and quality of differentiated instruction and to determine how providing DI could be trained and assessed in practice, the literature has been reviewed for instruments that researchers have used to measure the quality or degree of differentiation, as the construction of such instruments requires an explicit operationalization of teacher behavior.…”
Section: Differentiation As Part Of Teaching Qualitymentioning
confidence: 99%
“…Yet now, the concept of differentiated instruction is also commonly applied in more cognitive scholarly approaches which focus, for instance, on the learning effect of differentiated instruction (e.g. Deunk, Doolaard, Smale-Jacobse, & Bosker, 2015;Prast, Weijer-Bergsma, Kroesbergen, & Luit, 2015). Following Tomlinson, teachers must carefully consider which teaching strategy is appropriate at which particular moment for a particular group of students.…”
Section: Differentiated Instructionmentioning
confidence: 99%
“…A solid understanding of the learning goals and developmental progression in each subject or skill is required, as are methods for achieving and using a differentially implemented curriculum including learning materials (Deunk et al 2015;Mooij et al 2014;Tomlinson et al 2003). Learning processes can be evaluated and managed in order to provide for further learning steps.…”
Section: Anticipating Student Differencesmentioning
confidence: 99%
“…Regular monitoring of levels and progress is necessary so that teachers may continually modify free play and instruction and vary grouping patterns to meet changing characteristics and needs (Deunk et al 2015;Purcell et al 2002).…”
Section: Anticipating Student Differencesmentioning
confidence: 99%